Effect of acetic acid fermentation modes in pottery jar and stainless-steel pool on the quality of Shanxi aged vinegar - GAO Cuimei, KANG Shuaishuai, WEI Ruteng, LI Qi, LI Yunlong, ZHANG Xiaoyu, XU Nv (Zhongguo niangzao, 2025)
In order to study the effect of two acetic acid fermentation modes in traditional handmade pottery jar (pottery jar) and large mechanical stainless- steel pool (stainless-steel pool) on quality of Shanxi aged vinegar, the temperature and physicochemical indexes during acetic acid fermentation were monitored, and the basic physicochemical indexes, organic acids, amino acids and volatile aroma components contents of new leaching vinegar were analyzed. The results showed that under the two fermentation modes, the temperature during acetic acid fermentation rose first and then fell, the total acid increased, the alcohol content decreased, the moisture decreased first and then increased and tended to be stable, while the acetic acid fermentation period of pottery jar was shorter. Compared with the new leaching vinegar in the stainless-steel pool, the soluble unsalted solids (8.63 g/100 ml), the total contents of amino acids (4.72 mg/ml), and the total contents of volatile aroma components (15.25 mg/100 ml) of new leaching vinegar in pottery jar increased by 5.79%, 20.12%, and 4.27%, respectively, and the total contents of organic acids decreased by 25.48%. The contents of oxalic acid and malic acid increased by 59.73% and 63.48%, respectively, while the contents of tartaric acid, lactic acid and citric acid decreased by 53.73%, 57.84%, and 86.55%, respectively; The total contents of essential amino acids increased by 21.19%; The contents of acids, pyrazines and other substances in volatile aroma components increased by 55.08%, 45.05%, 52.19%, respectively, while the contents of alcohols and ketones decreased by 45.11% and 95.13%, respectively. The quality and flavor of new leaching vinegar in the traditional handmade pottery jar were better than that in the large mechanical stainless-steel pool, but the large mechanical stainless-steel pool could achieve large-scale production.